Novel benzopyran derivatives and their therapeutic applications: a patent review (2009–2016). (2nd September 2017) - Xiu, Cheng; Hua, Zhou; Xiao, Bao sheng; Tang, Wen Jian; Zhou, Hai Pin; Liu, Xin Hua
ABSTRACT: Introduction : The benzopyran derivatives present a wide variety of biological activity and behaviour. At the same time the benzopyran derivatives support their use as therapeutic agents for multiple diseases. Their structural characteristics correlated to physicochemical properties seem to define the extent of the biological activity. Areas covered : This review summarizes new patents published on new benzopyran derivatives from 2009 to 2016. Expert opinion : Many benzopyran derivatives have vivo / vitro biological responses. Their clinical evaluation will be critical to assess therapeutic utility. The compounds containing benzopyran moiety is well defined as lead compounds for design of new more promising molecules.